The Contributions of Political Science to Processes of Institutional Political Change: The Case of Chile - Figueroa-Rubio, P (UNIV COMPLUTENSE MADRID, SERVICIO PUBLICACIONES, 2024)
This article examines the role of political scientists in the process of political change in Chile, considering the political reforms implemented between 2006 and 2020. Chile has stood out in comparative studies as a stable democracy, but since the 2010s the political system has been affected by a crisis of legitimacy and trust. The response to this crisis has been a path of legal reforms, and three attempts at constitutional change since 2016 to date. Throughout this process of political change, expert knowledge has been highly valued, and political scientists have been called upon to contribute their own knowledge and vision. This coincides with the consolidation of political science as a discipline since the 2000s. Thus, for the study of the contributions of political science to society, three indicators are considered: positioning, degree of influence and prestige, which will be applied to three cases: the design of the reform of the electoral system in 2006, the political reforms in 2014, and the constituent process and the innovation of the election of a parity constituent body in 2020.